Peran Kepemimpinan Kepala Sekolah sebagai Motivator dalam Manajemen Pengembangan Budaya Islami di SMA Pesat Kota Bogor - Khairul Umam; Endin Mujahidin; Maemunah Sa’diyah (Mudir : Jurnal Manajemen Pendidikan, 2023)
To achieve success, every educational institution requires good management. One way is to make management arrangements, so that the process of developing Islamic culture can take place effec-tively and efficiently. This study aims to analyze planning, organizing, driving and supervising management in SMA Pesat Bogor City. This paper is a qualitative research that conducts in-depth observations at the Pesat High School in Bogor City. Data collection techniques are carried out through interviews, observation, and documentation studies. The results obtained show that man-agement and planning activities started with deliberations held with the vice principal and teachers to design the RKT and RKJM; organizing in the form of dividing tasks and roles with school mem-bers; mobilization carried out in the form of motivation and guidance to produce Islamic culture including in fostering morals, worship, and Islamic learning content; and supervision in the form of follow-up with rewards and punishments.